Results Of Immunological Studies of Patients with Viral Encephalitis with Symptomatic Epilepsy - Khojimatova Malika Shukhratovna (Zien Journals, 2021)
Viral encephalitis is an acute process in the central nervous system, which in most cases of the disease is recorded in adults with chronic recurrent mixed infection. In parts of the brain, viruses can be a source of replicative relapses of chronic viral neuroinfection with the development of symptomatic epilepsy resistant to antiepileptic therapy
Keywords: Viral neuroinfection; Viral encephalitis; Central nervous system; Antiepileptic therapy